Male sexual tourism in Costa Rica: team spirit, peer dialogue and gender roles in a large sample of Internet forum posts (UNED Research Journal, 2016)
There are few scientific studies about sexual tourism in Costa Rica. The most important study about male tourists, done by Megan Rivers-Moore, presented a series of hypotheses. Here I analyze all forum posts in the InternationalSexGuide.info from 2002 through 2015, and compare them with Rivers-Moore’s hypotheses, the Intimacy Prism categories of Milrod and Weitzer and with female sex tourists (as reported in the literature). The 4 409 reports show that men interact in peer dialogues in which they mostly advise each other about how to get a satisfactory visit to Costa Rica: a visit that includes paid sex but is not limited to it. While sex working women have little interaction among themselves, these men feel part of a group and exchange useful information. The desire for a Girl Friend Experience, though not predominant, is frequent and fits biological adaptations for mate interactions among humans. Male tourists mostly make short visits in which they try to meet a few women and then focus on those that make the best impression. A few evolve into complex relationships that include emotional commitment. Despite the financial disparity between men and women, traditional gender roles underlie the relationships of both male and female tourists, probably reflecting a complex combination biological and cultural factors.
Keywords: Gender interactions in sex work; Latin American sexuality; prostitution; internet culture